Kansei Engineering Application of Non-heritage Floral Pattern in Modern Women's Bag Design - Daiyun YU; Benhui REN; Shuang XIE (Pige Kexue Yu Gongcheng)
In order to explore the perceptual cognitive expression of intangible cultural heritage wrapped flower patterns and their regenerative design on modern women's bags, 15 intangible cultural heritage wrapped flower patterns were selected based on the principle of Kansei engineering, and the stimulus map was drawn by drawing software. 12 pairs of perceptual evaluation description words were selected and determined, and a questionnaire was designed for investigation. The questionnaire was distributed to women aged 25-40. SPSS software was used to carry out mean analysis, factor analysis and cluster analysis of the survey data. Through the shape pattern evolution rule, typical samples were selected while factor database was established, and design elements were extracted and integrated into the modern women's bag design. The results show that the perceptual factors affecting the intangible cultural heritage pattern are visual factors and modeling factors, respectively. The pattern with the highest degree of satisfaction was selected to be applied to the design of modern women's bag, and the design of intangible cultural heritage pattern for women's leather bag was harmonious and unified, which is conducive to promoting the organic combination of intangible cultural heritage pattern and modern women's bag design.